Identification of the second common Jewish Gaucher disease mutation makes possible population-based screening for the heterozygous state. - Beutler, E (1991)
Gaucher disease is an autosomal recessive glycolipid storage disease characterized by a deficiency of glucocerebrosidase. The disease is most common in persons of Ashkenazi Jewish ancestry and the most common mutation, accounting for about 75% of the mutant alleles in this population, is known to be an A----G substitution at cDNA nucleotide (nt) 1226. Screening for this disease has not been possible because nearly 25% of the mutant alleles had not been identified, but linkage analysis led to the suggestion that most of these could be accounted for by a single mutation. We now report the discovery of this mutation. The insertion of a single nucleotide, a second guanine at cDNA nt 84 (the 84GG mutation), has been detected in the 5' coding region of the glucocerebrosidase gene. The amount of mRNA produced is shown to be normal but since the frameshift produced early termination, no translation product is seen. This finding is consistent with the virtual absence of antigen found in patients carrying this mutation. The 84GG mutation accounts for most of the previously unidentified Gaucher disease mutations in Jewish patients. The common Jewish mutation at nt 1226, the 84GG mutation, and the less-common mutation at nt 1448 accounted for 95% of all of the Gaucher disease-producing alleles in 71 Jewish patients. This now makes it possible to screen for heterozygotes on a DNA level with a relatively low risk of missing couples at risk for producing infants with Gaucher disease.